Institutions, Shared Guilt, and Moral Transgression - Dominik Rothenhäusler; Nikolaus Schweizer; Nora Szech (Center for Economic Studies and ifo Institute (CESifo), 2015)
Many tasks can only be completed if several people contribute. Likewise, many institutions, e.g. voting rules, require the support of several people to implement specific decisions. In such situations, individual costs from supporting may decrease in the number of supporters. This holds true for physical costs in division of labor. Psychological, sociological and economic evidence suggests that also moral costs due to feelings of guilt or having a bad conscience diffuse. This paper analyzes the influence of diffusion of costs in threshold public good games under incomplete information, and compares predictions to those when costs do not diffuse.
Keywords: D02; D03; D23; D63; D82; 330; moral decision making; division of labor; shared guilt; diffusion of responsibility; institutions and morals; committee decisions; moral transgression